Rola Awarów w rozpowszechnieniu w Europie azjatyckich form uzbrojenia - Świętoslawski, Witold (Acta Universitatis Lodziensis. Folia Archaeologica, 2001)
As a result of influx of Avars to the central Europe in the 4th century' earlier unknown forms of armament reached our continent. As an example may serve an attractive head protecting helmet made of plates found in Niederstotzingen (Germany) (fig. 1A). It was dated to the 7th century. The oldest specimens of this sort of helmets come from South Korea (fig. 1 B). Their chronology was defined as second part of the 5th century. Numerous Asiatic analogies can be observed in case of broad, one-edged swords (pałasz) with ring heads found in Hungary in Avar graves coming from the 7th century (fig. 2 D). Their Far East analogies come mainly from south Korea and are dated to the 2nd half of the 5th and 1st half of the 2nd century (fig. 2 A-В). Younger specimens found in the Black Sea steppe in the eastern Europe, central Asia and west Siberia (fig. 2 C) are dated to the first centuries of the Middle Ages. Broad, one-edged sword (pałasz) was a basic form of long side-arms in the territory of Persia through central Asia to the Far East. In these territories it replaced earlier used sword. However pałasz lost its meaning and popularity after a sabre, a new type of side-arms, became popular. A sabre was the most popular type of long side-arms among the people of the Great Steppe. At present the question whether it originated from Asia or Europe can not be answered. The oldest known sabres originate from the 7th-8th centuries and come from the graves of Avars’ found in the territory of Hungary and the Black Sea steppes. So far no Asiatic sabres from those early times have been found. A sabre appeared useful and became popular among the steppe people who used high saddle with stirrups. Both saddles and stirrups were used by those nomads who migrated in the Asiatic part of the Great Steppe. A stiff wooden-leather saddle with clearly distinguished pommel (fig. 3) is an example of early Mediaeval central and west European saddles, which is confirmed by archaeological finds. Undoubtedly, this type of saddle has an Asiatic provenience. The oldest saddles of this type were found in the territories of the present China and Korea. They come from the 4th-5th centuries. They already have high wide pommels. Their shape is analogous to the forms of remnants of saddles found in the territory of present Hungary in the graves of Avars’ from the 7th century. Particularly important role in popularising stirrups in the territory of Europe and Asia was played by early Mediaeval steppe nomads. Finds of the earliest dated stirrups come from the are of present Korea and from north-eastern China. They are dated to the 2nd half of the 4th century. At the turn of the 5th century stirrups from the Far East were adopted by the nomads from the mid-Asian steppes. Whereas the oldest specimens of European stirrups, dated to the 1st half of the 7th century were found on the cemeteries of Avars’ in Hungary (fig. 5A).They have analogies among Chinese stirrups coming from the same period of time. A representation of a stirrup on a relief on the plate of the emperor Tayzung’s tomb (627-649) (fig. 5B) is an evidence. Among presented above Asiatic forms of armament predominate finds which have close analogies in distant from Europe territories of the Far East. Their occurrence in Europe at the beginning of the Middle Ages should undoubtedly be connected with the nomads of the Great Steppe. The Avars had an important influence on shaping new Mediaeval European armament, in many ways different from the ancient tradition.